Bioaktivitas Ekstrak N Heksan Umbi Ubi Jalar AC Kuningan (Ipomoea batatas) Dalam Menghambat Pertumbuhan Beberapa Patogen Dan Pemanfaatannya Untuk Fortifikasi Makanan - Ilah Nurlaelah (BIO-SITE |Biologi dan Sains Terapan, 2016)
AC kuningan sweet potato (Ipomea batatas) is one of the endemic plants in Kuningan district which became the biggest commodity. Sweet potato tuber is a food rich in vitamins and minerals that include beta carotene, polyphenols, vitamin B1, vitamin C, calcium, phosphorus, iron, potassium and sodium. This study aimed to obtain the best concentration of n-hexane extract of AC Kuningan sweet potato tubers (Ipomea batatas) in inhibiting the growth of some pathogens from the type of potato AC red and white AC Kuningan tested against microbes in the form of selected bacteria comprising E. coli, Bacillus sp and Staphylococcus sp collection of FKIP UNIKU biology laboratory, determined the content of polyphenols and antioxidant activity as well as the potential for the best formula in the sweet potato flour fortified biscuits. The method used was experimental laboratory. Data on antibacterial bioactivity was measured by paper disc diffusion method, analysed chemical compounds through spectrophotometer polyphenols and antioxidant activity with DPPH method. Analysis of the data was used for testing antibacterial that was ANOVA test. Determining the level of preference for the value of biscuit products was using hedonic test and Freadment. The results showed that the highest inhibitory potency extract of n-hexane potato red AC shown at a concentration of 2000 ppm n-hexane while to extract the white yam AC shown at a concentration of 500 ppm. Both types of potato AC Brass had fairly high polyphenol content for sweet potatoes 356.78 ± 19.25 ppm and white potatoes 206.72 ± 6.90 ppm and antioxidant activity with IC50 values are shown respectively in figures 1759.89 ± 1793.60 ± 7.18 ppm and 25.41 ppm was beneficial to fight free radicals. Test formulation 1 ranking indicated that it wasmore desirable biscuits by panelists in terms of taste, texture, color and aroma. It showed sweet potato flour helpful for fortifying foods that had nutritional value and better flavor.